2018
DOI: 10.1186/s12929-018-0417-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtyping of nasopharyngeal carcinoma (NPC) and a microRNA-based prognostic model for distant metastasis

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is a highly invasive and metastatic cancer, with diverse molecular characteristics and clinical outcomes. This study aims to dissect the molecular heterogeneity of NPC, followed by the construction of a microRNA (miRNA)-based prognostic model for prediction of distant metastasis.MethodsWe retrieved two NPC datasets: GSE32960 and GSE70970 as training and validation cohorts, respectively. Consensus clustering was employed for cluster discovery, and support vector machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Unfortunately, the anti-programmed cell death protein 1 (PD-1) therapies benefit only a subset of patients, while there is no strong evidence of the well-established ICI biomarkers in NPC [ 3 ]. Tumour gene expression profiles represent important resources to model the TME status and identify potential biomarkers [ 4 , 5 ]. In this study, we unraveled the TME heterogeneity based on gene expression profiles, and identified the distinct Active, Evaded and non-Immune Subtypes (A-IS, E-IS and non-IS) in NPC (Additional file 1 : Figure S1).…”
Section: Backgroudmentioning
confidence: 99%
“…Unfortunately, the anti-programmed cell death protein 1 (PD-1) therapies benefit only a subset of patients, while there is no strong evidence of the well-established ICI biomarkers in NPC [ 3 ]. Tumour gene expression profiles represent important resources to model the TME status and identify potential biomarkers [ 4 , 5 ]. In this study, we unraveled the TME heterogeneity based on gene expression profiles, and identified the distinct Active, Evaded and non-Immune Subtypes (A-IS, E-IS and non-IS) in NPC (Additional file 1 : Figure S1).…”
Section: Backgroudmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is one of the most common head and neck malignancies, which can be easily induced by environmental factors, genetic factors, and EB virus infection [1, 2]. NPCs have the pathological characteristics of high incidence, rapid deterioration, and poor prognosis and most NPC patients have developed to the middle- and late-stage by the time of diagnosis [3, 4]. Radiotherapy is dominated in the treatment of NPC due to the high sensitivity, but NPC cells are prone to distant metastasis and recurrence after treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…As an effective and commonly used cancer treatment and the standard therapeutic intervention for various malignant tumors, IR causes DNA damage and destroys cancer cells to achieve its therapeutic effects [25]. Despite the high radiosensitivity of bulk cells, the existence of radioresistant cells in NPC tissue, however, lead to NPC recurrence and metastasis after radiation [26,27]. In this study, we found that NPC cells with lower expression of miR-34c displayed less sensitivity to irradiation, which contribute to the radioresistance of NPC in clinic.…”
Section: Discussionmentioning
confidence: 99%